Deprivation, low birth weight, and children's height: a comparison between rural and urban areas. Issue 6917 (4th December 1993) - Reading, R; Raybould, S; Jarvis, S
Abstract : OBJECTIVE–To compare proportions of low birthweight babies and mean heights of schoolchildren between rural and urban areas at different levels of social deprivation. DESIGN–Cross sectional population based study classifying cases by Townsend material deprivation index of enumeration district of residence and by rural areas, small towns, and large towns. SETTING–Northumberland Health District. SUBJECTS–18, 930 singleton infants delivered alive during January 1985 to September 1990 and resident in Northumberland in October 1990; 9055 children aged 5 to 8 1/2 years attending Northumberland schools in the winter of 1989-90. MAIN OUTCOME MEASURES–Odds ratios for birth weight less than 2800 g; difference in mean height measured by standard deviation (SD) score. RESULTS–Between the most deprived and most affluent 20% of enumeration districts the odds ratio for low birth weight adjusted for rural or urban setting was 1.71 (95% confidence interval 1.51 to 1.93) and the difference in mean height -0.232 SD score (-0.290 to -0.174). Between large towns and rural areas the odds ratio for low birth weight adjusted for deprivation was 1.37 (1.23 to 1.53) and the difference in mean height -0.162 SD score (-0.214 to -0.110). Results for small towns were intermediate between large towns and rural areas. CONCLUSIONS–Inequalities in birth weight and height exist in all rural and urban settings between deprived and affluent areas. In addition, there is substantial disadvantage to living in urban areas compared with rural areas which results from social or environmental factors unrelated to current levels of deprivation.